Extracellular vesicles mediate cellular interactions in renal diseases—Novel views of intercellular communications in the kidney. Issue 8 (11th January 2021) - Zhang, Ping L.; Liu, Ming‐Lin
Abstract: The kidney is a complicated and important internal organ receiving approximately 20% of the cardiac output and mediates numerous pathophysiologic actions. These include selectively filtering macromolecules of the blood, exquisite reclaimation of electrolyctes, urine concentration via an elegant osmotic mechanism, and excretion of an acid load. In addition, the renal tubules carry out secretory functions and produce hormones and cytokines. The kidney receives innervation and hormonal regulation. Therefore, dysfunction of the kidney leads to retention of metabolic waste products, and/or significant proteinuria and hematuria. In the past several decades, the role of extracellular vesicles (EVs) in intercellular communications, and the uptake of EVs by recipient cells through phagocytosis and endocytosis have been elucidated. The new knowledge on EVs expands over the classical mechanisms of cellular interaction, and may change our way of thinking of renal pathophysiology in the subcellular scale. Based on some ultrastructural discoveries in the kidney, this review will focus on the role of EVs in intercellular communications, their internalization by recipient cells, and their relationship to renal pathology. Graphical abstract: In the past several decades, the role of extracellular vesicles (EV) in intercellular communications, and the uptake of EVs by recipient cells through phagocytosis and endocytosis have been elucidated. The new knowledge on EVs expands over the classical mechanisms of cellular interaction, and may change our way of thinking of renal pathophysiology in the subcellular scale. Based on some ultrastructural discoveries in the kidney, this review will focus on the role of EVs in intercellular communications, their internalization by recipient cells, and their relationship to renal pathology.